2016
DOI: 10.1177/0954008316660367
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal kinetics and thermodynamics studies of curing reaction of epoxy-aromatic diamine reinforced with epoxy functional MWCNT

Abstract: This study reports the cure kinetics and thermodynamics of an epoxy functional multiwall carbon nanotube-containing epoxy nanocomposite obtained by the polymerization of diglycidyl ether of bisphenol A with diaminodiphenyl sulfone as a curing agent through isothermal technique of differential scanning calorimetry. Isothermal kinetic parameters including reaction orders ( m, n), rate constants ( k1, k2), activation energy ( Ea), and pre-exponential factor ( A) were estimated using Kamal autocatalytic model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Presence of filler with reactive functionalities on the exterior increases their probability of covalent connection with polymer matrix 5–12 . This interaction between matrix and filler has experimental proof in the form of extra heat evolved 13 and fast rate of reaction, 14,15 in comparison to reaction without filler.…”
Section: Introductionmentioning
confidence: 92%
“…Presence of filler with reactive functionalities on the exterior increases their probability of covalent connection with polymer matrix 5–12 . This interaction between matrix and filler has experimental proof in the form of extra heat evolved 13 and fast rate of reaction, 14,15 in comparison to reaction without filler.…”
Section: Introductionmentioning
confidence: 92%
“…5,6) Because amine is the most commonly used epoxy hardener, numerous researches have been dedicated to the effects of GO or carbon nanotube on the cure kinetics of epoxy-amine systems; and it has been reported that nanocomposite properties are highly dependent on how GO or carbon nanotubes affect the curing behavior of the epoxyamine matrix. 7,8) For example, they could catalyze the curing process and influence the network formation of the resin, or act as a physical hindrance that inhibits the cure process. Acid anhydrides are the second most commonly used epoxy hardeners, but their curing mechanism (chain-wise) is quite different from that of amine-hardeners (stepwise).…”
Section: Introductionmentioning
confidence: 99%
“…5 CNTs-reinforced polymer matrices became attractive structural composite materials for various industries such as aerospace, automobile, marine, defense armor, civil engineering, and sporting goods. [6][7][8][9][10][11][12][13][14] Epoxy-CNT nanocomposites were first time reported in 1994 15 and thereafter many researchers' reported the improved thermal and mechanical properties of the epoxy-CNT nanocomposites. [16][17][18][19] CNTs are generally nonreactive because of their defect-free smooth structure of sidewall aromatic rings.…”
Section: Introductionmentioning
confidence: 99%